Leveling Up English Writing Skill: The Role of Gamification in Language Education - Satriani Satriani; Rafi’ah Nur; Salasiah Ammade; Ammang Latifa; Siti Hajar Larekeng (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
Integrating game aspects into non-gaming environments, or "gamification," has become a potent technique in education that can make conventional teaching methods more engaging. Gamification has shown promise in the field of language education for improving a variety of skills, including writing. This study aimed to know whether the use of the gamification teaching method has a significant effect on the students’ writing skills and their attitudes toward the method. This study used a pre-experimental method with a one-group pre-test and post-test design. A writing test was used to determine the students’ writing skills before and after using the gamification teaching method. Meanwhile, a questionnaire was used to determine the students’ attitudes toward the method. The result of this study shows that the mean score of the pre-test was 52.5714, and the mean score of the post-test was 70.2875. The result of the questionnaire also indicates that the use of the gamification teaching method helps students write descriptive texts and engages them in the learning process. It can be inferred that students' writing skills have improved, and they exhibit a highly positive attitude when taught using the gamification teaching method.